Yo-kai watch. 3, Jibanyan's tale - Konishi, Noriyuki; Sitterson, Aubrey (VIZ Media, LLC, 2016)
Elementary student Nate Adams sees Yo-kai all around him thanks to his Yo-kai watch. Soon he, Whisper, and Jibanyan become involved in all kinds of ghostly adventures with other Yo-kai.